(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: This study was carried out to assess whether delayed cord clamping is effective in improving the haematological status of term infants born to anemic mothers and whether this is associated with complications in infants and mothers. Methods: we randomly assign women delivering vaginally term babies in Lady Willingdon Hospital Lahore to immediate cord clamping (ICC, n=100) or delayed cord clamping (DCC, n=100) and follow their infants until the age of 3months. We compared infant hemoglobin change from cord value. Secondary outcomes were related to infant and maternal safety. Results: infant hemoglobin level at b3months declined in both groups but more in group of immediate cord clamping. Mean infant Hb at 3months in ICC group was and bin DCC group was. Difference of Mean infant Hb in ICC group was and in DCC group was. No adverse events were seen in infants and mother. Conclusion: DCC improved the heamatological status of term infants born to anemic mothers. It is a simple, safe and cost free intervention to reduce early infant anemia risk.